2020
DOI: 10.1111/aab.12635
|View full text |Cite
|
Sign up to set email alerts
|

A thorough study of a Paratylenchus sp. in glasshouse‐grown lettuce: Characterisation, population dynamics, host plants and damage threshold as keys to its integrated management

Abstract: In glasshouses practising monoculture of butterhead lettuce in Belgium, high densities of pin nematodes (Paratylenchus spp.) are frequently associated with reduced plant growth. Growers currently apply chemical soil disinfestation measures to manage this problem, although stricter phytosanitary regulations are forcing a shift towards integrated management. Efficient implementation of such management requires knowledge about the factors influencing nematode population dynamics, and the damage threshold for lett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
(54 reference statements)
2
8
0
Order By: Relevance
“…The species was first found (but not described) in the glasshouse-grown lettuce from Belgium. The species causes damage to the root system, but this was not related to significant yield reduction in lettuce heads [34]. In the present study, same species was found in the potato growing region of southern Alberta.…”
Section: Remarkssupporting
confidence: 65%
See 2 more Smart Citations
“…The species was first found (but not described) in the glasshouse-grown lettuce from Belgium. The species causes damage to the root system, but this was not related to significant yield reduction in lettuce heads [34]. In the present study, same species was found in the potato growing region of southern Alberta.…”
Section: Remarkssupporting
confidence: 65%
“…Lower densities of identified species in the samples suggest that these are mild parasitic species and, as of yet, do not behave as potential pests. However, pin nematodes have a reputation of building high population densities in short periods, and, under favorable circumstances, can be a threat to their hosts [22,34]. Indeed, a higher incidence of root lesion nematodes (Pratylenchus spp.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This species has been recently described from Canada [ 21 ]; and it has also been reported in Belgium [ 22 , 24 ]. In the present study, the P. enigmaticus population from Spain matches with the original species description, except for minor differences in body length and a ratio; the Spanish population is slightly shorter than the original one (324–383 µm vs. 343–431 µm) and with smaller a ratio (17.6–21.6 vs. 21.7–28.7) ( Table 6 , Figure 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pathogenicity has been found only on different crops for a few species such as P. bukowinensis Micoletzky, 1922 in celery ( Apium graveolens L.) [ 8 , 9 ]; Paratylenchus dianthus Jenkins & Taylor, 1956 in carnation ( Dianthus caryophyllus L.) [ 10 ]; Paratylenchus epacris (Allen & Jensen, 1950) Goodey, 1963 in black walnut ( Juglans nigra L.) [ 11 ]; Paratylenchus hamatus Thorne & Allen, 1950 in fig ( Ficus carica L.), pear ( Pyrus communis L.) and grapevine ( Vitis vinifera L.) [ 12 , 13 , 14 ]; Paratylenchus microdorus Andrassy, 1959 in red clover ( Trifolium pratense L.) and lettuce ( Lactuca sativa L.) [ 15 ]; Paratylenchus nanus Cobb, 1923 in garden balsam ( Impatiens balsamina L.) [ 16 ]; Paratylenchus neoamblycephalus Geraert, 1965 in Myrobalan plum ( Prunus cerasifera Ehrh.) [ 17 ]; Paratylenchus projectus Jenkins, 1956 in alfalfa ( Medicago sativa L.) and sunflower ( Helianthus annuus L.) [ 18 , 19 ]; Paratylenchus shenzhenensis Wang, Xie, Li, Xu, Yu & Wang, 2013 in Anthurium andraeanum Linden ex André [ 20 ]; and Paratylenchus enigmaticus Munawar, Yevtushenko, Palomares-Rius & Castillo, 2021 in lettuce [ 21 , 22 ]. Other species can be also pathogenic in crops, but further studies are necessary to confirm this.…”
Section: Introductionmentioning
confidence: 99%